Prosedur Pemeriksaan CT Scan Abdomen Pada Kasus Kolesistitis di Instalasi Radiologi RSUD Prof. Dr. Margono Soekarjo Purwokerto - Titien Sumarni; Bagus Abimanyu; Dartini Dartini (Poltekkes Kemenkes Semarang, 2015)
Background: Have been done research on inspection procedures examination in the case of abdominal CT Scan cholecystitis at Radiology installationProf. Dr. Margono Soekarjo Purwokerto Hospital. This study aims to determine the inspection procedure examination in the case of abdominal CT Scan cholecystitis not using the biphase technique diagnosis and to find out information on examination in the case of abdominal CT Scan cholecystitis with monophase technique at Radiology installationProf. Dr. Margono Soekarjo Purwokerto Hospital.Methods:This type of research is aqualitaive research case study approach. The data collection methods with unstructured observation , depth interview with 3 radiographers, 1 radiologist, a sending doctor and a patient, and the documentation of the results of reading radiographs and photographs. The data obtained then reduced, classified, dried and then interpreted in the form then concluded kuotasi and suggestions.Results: The result showed that the procedure examination abdomen ct scan in case of colecystitis at radiology installation Prof. Dr. Margono Soekarjo Purwokerto Hospital before the hearing preparation charge informed consent of patients, perform laboratory checks urium creatinin, fasting from the night and drank appoxcimately 1000 ml of Water the morning before the examination. While the position of the patient supine feet first and the administration of contrast media intra vena with a volume of 80 ml plus 20 ml Na Cl and arrangements flow rate 2,0 ml/sec with a scan delay of 40 seconds. Reason not to do engenering biphase technique examination in the case of abdominal CT Scan cholecystitis because only monophase technique, arterial phase alone can establish the diagnosis of cholecystitis.Conclusion: Information on CT Scan diagnosis in Radiology Installation Prof. Dr. Margono Soekarjo Purwokerto Hospital was able to show in indication of cholecystitis but have not been able to show the mass and metastase to the surrounding organs lake the liver gallbladder and pancreas, intrahhepatic and extrahepatic tract.